Evaluation of the physicochemical and microbiological quality of the water used by the animals in the Parque Municipal da Matinha, Itapetinga, Bahia, Brazil (Research, Society and Development, 2022)
This study aimed to evaluate the quality of the water used by the animals of the Parque Municipal da Matinha, Itapetinga, Bahia, through physical-chemical and microbiological analyses, observing the adequacy to the parameters established for class 3 waters described in CONAMA Resolution No. 357 / 2005. From July to October 2021, 60 water samples were collected from 15 environments (central tank, kitchen, lakes that surround the monkey islands (small island and large island), caimans, in addition to the drinking fountains present in different venues). The analyzes were performed using the analytical methodologies contained in the Standard methods for the examination of water and wastewater. The results indicate that the waters used by the animals of the Parque Municipal da Matinha, Itapetinga Bahia showed compliance in most of the physical-chemical parameters evaluated. The park's water supply samples complied with current legislation, that is, they were suitable for the animals to drink water. However, nonconformities were recorded in the microbiological parameters for most animal enclosures, thus indicating the need for increases in the frequency of cleaning and disinfection in the drinking fountains. The lakes evaluated revealed recent fecal contamination in the waters of these environments, in addition to nonconformities for some physical-chemical parameters. In this way, the renewal of these waters combined with a filtration system can improve their quality. Therefore, it is evident that the monitoring of the physical-chemical and microbiological quality of the waters used by the animals effectively contributes to the diagnosis and improvements in the management of the park.